2016
DOI: 10.1002/eqe.2758
|View full text |Cite
|
Sign up to set email alerts
|

An improved energy‐based approach for selecting pulse‐like ground motions

Abstract: Summary This study proposes an improved energy‐based approach for quantitative classification of velocity‐pulse‐like ground motions. The pulse amplitude is determined, in its value and in time location, by the amplitude of the half‐cycle pulse having the largest seismic energy. After conducting statistical analyses, a newly‐determined threshold level for selecting pulse‐like ground motions is derived; and then what followed is a comparison analysis of three pulse‐detecting schemes, one using the wavelet analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
117
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 78 publications
(124 citation statements)
references
References 15 publications
6
117
0
1
Order By: Relevance
“…Comparison of the T p calculated in the current study with those derived by (a) Chang et al. (), (b) Baker (), (c) S v , and (d) S d⋅ S v …”
Section: Proposed Approachmentioning
confidence: 52%
See 3 more Smart Citations
“…Comparison of the T p calculated in the current study with those derived by (a) Chang et al. (), (b) Baker (), (c) S v , and (d) S d⋅ S v …”
Section: Proposed Approachmentioning
confidence: 52%
“…This way of using WPT for deriving T p is then compared with those in Baker (), Chang et al. (), the S v , as well as S d ⋅ S v methods. In Figure , the comparative results are shown in terms of scatter plots, reporting the correlation coefficients (ρ) between the T p estimates based on the different studies.…”
Section: Proposed Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, the seismic damage within a near-fault region is often caused during a few cycles of severe inelastic deformation that coincides with large amplitude velocity pulses in the ground motions. [11][12][13] From the engineering perspective, the effects of pulse-like ground motions on various structures have been investigated, including idealized single (or multi)-degree-of-freedom (SDOF) systems, 14,15 seismically base-isolated structures, 16,17 bridge structures, 18,19 and some other special buildings or elements. 2 Previous studies confirmed that key features of the velocity pulse, eg, amplitude, predominant period, and the pulse shape, play important roles in affecting the structural response and are primarily affected by the earthquake source characteristics, location of the recording station relative to the fault rupture as well as the site effects.…”
Section: Introductionmentioning
confidence: 99%